2019
DOI: 10.1097/md.0000000000014637
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of polaprezinc on cardiac function post-myocardial infarction

Abstract: Background:Polaprezinc is clinically used for the treatment of gastric ulcers. It induces the mobilization of mesenchymal stem cells and the mRNA expression of insulin-like growth factor-1 in vascular endothelial cells in order to protect injured gastric tissue or skin.Methods:The current study population included 50 patients with primary acute myocardial infarction (AMI). After percutaneous coronary intervention, the subjects were randomly divided into 2 groups, namely, the nonpolaprezinc and polaprezinc grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Polaprezinc is a chelated form of zinc and L -carnosine that shows therapeutic activity for the treatment of pressure ulcers and other intestinal lesions [ 61 , 62 ], is used in cancer chemotherapy [ 63 , 64 ], presents therapeutic effects on cardiac function [ 65 ] and has a protective effect against respiratory diseases [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polaprezinc is a chelated form of zinc and L -carnosine that shows therapeutic activity for the treatment of pressure ulcers and other intestinal lesions [ 61 , 62 ], is used in cancer chemotherapy [ 63 , 64 ], presents therapeutic effects on cardiac function [ 65 ] and has a protective effect against respiratory diseases [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that polaprezinc is not absorbed by normal epithelium, but it adheres to and infiltrates ulcer regions, inducing the activation of mesenchymal stem cells and the production of insulinlike growth factor-1 in vascular endothelial cells, and has wound healing-promoting effects and antiulcer actions to protect damaged gastric tissue and skin 21,22 . Regarding its antioxidant actions, it has been reported that polaprezinc removes free radicals in inflammatory regions; moreover, antioxidant markers, such as superoxide dismutase-1, superoxide dismutase-2, heme oxygenase-1, peroxiredoxin-1, and peroxiredoxin-V, have been reported to be increased in the rat model of polaprezinc treatment 23 .…”
Section: Discussionmentioning
confidence: 99%
“…1), 5 studies were excluded for the following reasons: unavailable data, inappropriate study design, and unrelated outcomes. At the end of the selection process, 14 studies [5,22,33,[48][49][50][51][52][53][54][55][56][57][58] meeting the inclusion criteria were eventually selected for systematic review and meta-analysis. The PRISMA checklist is presented as a Supplementary File.…”
Section: Study Search and Selectionmentioning
confidence: 99%
“…Table 2 (Ref. [5,22,33,[48][49][50][51][52][53][54][55][56][57][58]) and Supplementary Table 1 list the basic characteristics of the studies that were included. These studies were published between 2011 and 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation